An Analysis of Factors Influencing Career Transitions Among Emergency Physicians in Taiwan - Hsu, Kuo-Fang; Huang, Ping-Lung; Lee, Bruce C.Y.; Wang, Chen-Song (Journal of Posthumanism, 2025)
This study investigates the factors influencing career transitions among emergency physicians in Taiwan, focusing on critical issues such as work pressure, workplace culture, and development opportunities. Through a combination of literature review and the DEMATEL method, the study employs expert questionnaires to analyze the key determinants of emergency physicians’ turnover intentions and their interrelationships. The findings indicate that work pressure and burnout are primary factors, closely associated with work-life imbalance and perceived discrepancies in compensation. Additionally, legal risks and limited career development options serve as significant drivers. The study emphasizes that optimizing compensation structures, improving work environments, and providing interdisciplinary training (e.g., legal, engineering, financial management) could effectively enhance physician retention. These insights offer valuable references for policymakers aiming to support the sustainable development of the emergency medicine field.